Host factor Rab4b mediates internalization and intoxication of 3D4/21 cells by the active subunit of the Glaesserella parasuis cytolethal distending toxin via influencing EEA1 expression - Zhang, Yiwen; Yang, Zhen; Du, Senyan; Zhao, Qin; Huang, Xiaobo; Wu, Rui; Wang, Yiping; Yan, Qigui; Cao, Sanjie; Wen, Yiping (Frontiers in Microbiology, 2025)
BackgroundThe cytolethal distending toxin (CDT), a significant exotoxin, is closely linked to the pathogenicity of Glaesserella parasuis (GPS), but its pathogenic not yet fully elucidated. Previously, we identified Rab4b as a potential host factor contributing to the cytotoxicity of GpCDT through a whole-genome CRISPR/Cas9 screen technology, and subsequently confirmed its association with GpCDT cytotoxicity in PK-15 cells.AimsIn this study, our data first indicated that Rab4b could interact with the active subunit of the Glaesserella parasuis cytolethal distending toxin.MethodsInvestigating the relationship between Rab4b and GpCDT subunits as confirmed by coimmunoprecipitation assay. Next, the porcine alveolar macrophage cell line 3D4/21 was used to establish an infected cell model. Using CRISPR/Cas9 gene editing, we established Rab4b and EEA1-expression-deficient 3D4/21 cell lines. 3D4/21 cells, Rab4b-KO cells and EEA1-KO cells were treated with GpCDT. Cell Counting Kit-8 (CCK-8) assay was used to detect cell viability. Western blotting and qRT-PCR were used to measure the expression of related proteins and genes, and cell morphology observation and indirect immunofluorescence were performed to evaluate the GpCDT-mediated cytotoxicity. Then utilise transcriptome sequencing analysis to investigate its specific mechanisms.ResultIn this study, our data first indicated that Rab4b could interact with the active subunit of the GpCDT. Next, we demonstrated that Rab4b also influences GpCDT-induced cytotoxicity and vesicle trafficking in 3D4/21 cells. To investigate the Rab4b-mediated cytotoxicity of GpCDT in 3D4/21 cells, we screened for EEA1, a gene critical in this process, by transcriptome sequencing analysis. 3D4/21 cells exposed to GpCDT exhibit upregulated EEA1 expression, an event that is lost in the absence of Rab4b. Using CRISPR/Cas9 gene editing, we established EEA1 expression-deficient 3D4/21 cell lines that fail to internalize GpCdtB, resulting in resistance to GpCDT-induced toxic effects.ConclusionsWe suggest that Rab4b facilitates the cellular uptake of GpCDTby upregulating EEA1 protein expression, thereby facilitating the vesicular transport of GpCDT in 3D4/21 cells. Our findings may provide new insights into the pathogenicity of GpCDT and lay the experimental foundation for a deeper understanding of the role of Rab4b proteins